2012
DOI: 10.1007/s12070-012-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body in Ear, Nose and Throat: Experience in a Tertiary Hospital

Abstract: To study the incidence of various foreign bodies in patients of different age and sex, attending E.N.T. Department, a retrospective review was done in Department of E.N.T., Burdwan Medical College and Hospital, Burdwan. About 334 patients with foreign body in ENT region presented to Department of E.N.T., Burdwan Medical College and Hospital from October 2008 to September 2010 were included in the study. Foreign body in ENT region is a common problem frequently encountered in both children and adults. Their acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 8 publications
8
21
1
Order By: Relevance
“…2.5% (5) were seen in greater than 60 age group. Similar results of 0-10 age group preponderance were seen in the study of Ray et al & Shreshtha et al 7,8 Children are common victims due to their tendency to put things in their natural orifices like ear, nose and mouth, inability to masticate well and inadequate control of deglutition, as well as the tendency to cry, shout, play during eating. Edentulous and poor masticating habits are predisposing factors.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…2.5% (5) were seen in greater than 60 age group. Similar results of 0-10 age group preponderance were seen in the study of Ray et al & Shreshtha et al 7,8 Children are common victims due to their tendency to put things in their natural orifices like ear, nose and mouth, inability to masticate well and inadequate control of deglutition, as well as the tendency to cry, shout, play during eating. Edentulous and poor masticating habits are predisposing factors.…”
Section: Discussionsupporting
confidence: 79%
“…There were similar finding by authors who reported higher incidence in male, but some reported no significant gender distribution. [5][6][7]10 In the present study, high proportion of FB were seen on right side 54 cases (52.4%) in case of FB ear and 39 cases (54.2%) in case of FB nose as compared to left side 46 cases (44.7%) in case of FB ear and 33 cases (45.8%) in case of FB nose with 3 cases (2.9%) of FB ear bilateral. Similar observation of right side laterality were made by Hon et al and Prayaga et al which postulated that it was contributed by right handedness.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Youngest child was 6 months old and the eldest was of 14 years, similar to results found in many other studies. [5][6][7][8][9] This may be due to the tendency of young children to lodge objects into the natural orifices of body, accidentally or intentionally. Foreign body ingestion is a common problem.…”
Section: Discussionmentioning
confidence: 99%
“…Many different foreign bodies have been discovered in the aural and nasal cavities of children presenting to the ED. These include food (particularly peas and corn), beads, toys, cotton tips, paper, jewellery and insects . Live insects in the ear are particularly distressing, and should be initially killed by instillation of oil (mineral oil or olive oil) or lignocaine solution…”
Section: What Is It? Does It Matter?mentioning
confidence: 99%